Characteristic and Defining Markers of PCOS - (:unkn) unknown (My University, 2024)
Polycystic Ovary Syndrome (PCOS) is one of the most frequently occurring endocrine disorders in women. The syndrome is diagnosed through a heterogeneous combination of androgen excess, anovulation, and ovarian dysfunction and is characterized by a host of resulting markers. This paper will paint the overall diagnostic picture of the condition and review a number of these markers to build an essential picture of PCOS. It will concentrate first on its principal metabolic markers then describe its physical, neurological and psychobehavioral markers. Each section will then abstract an essential picture from the data it presents. Finally, the review will conclude with a consolidation of the conclusions drawn in each section. The central theme that emerges is the inter-potentiated nature of PCOS markers.
Keywords: Polycystic ovary syndrome (PCOS); hyperandrogenism; central obesity; neuroticism; autonomic dysfunction.